2017
DOI: 10.31887/dcns.2017.19.2/rparikh
|View full text |Cite
|
Sign up to set email alerts
|

Cultural aspects of anxiety disorders in India

Abstract: Cultural factors have influenced the presentation, diagnoses, and treatment of anxiety disorders in India for several centuries. This review covers the antecedents, prevalence, phenomenology, and treatment modalities of anxiety disorders in the Indian cultural context. It covers the history of the depiction of anxiety in India and the concept of culture in the classification of anxiety disorders, and examines the cultural factors influencing anxiety disorders in India. We review the prevalence and phenomenolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 57 publications
(58 reference statements)
0
17
0
Order By: Relevance
“…For example, cultural factors were found to have a strong influence on variance in burnout and wellbeing in a study of large groups of medical students across 12 countries (Molodynski et al, 2021). Furthermore, culture has been found to be a determinant of anxiety and depression, with discrepant clinical trial results (Khambaty & Parikh, 2017; Kirmayer, 2001; Malik, 2021). Likewise, cultural response bias was found to be a contributing factor in the difference in subjective wellbeing among immigrants in Australia (Lai et al, 2013).…”
Section: Study Variables and Research Questionsmentioning
confidence: 99%
“…For example, cultural factors were found to have a strong influence on variance in burnout and wellbeing in a study of large groups of medical students across 12 countries (Molodynski et al, 2021). Furthermore, culture has been found to be a determinant of anxiety and depression, with discrepant clinical trial results (Khambaty & Parikh, 2017; Kirmayer, 2001; Malik, 2021). Likewise, cultural response bias was found to be a contributing factor in the difference in subjective wellbeing among immigrants in Australia (Lai et al, 2013).…”
Section: Study Variables and Research Questionsmentioning
confidence: 99%
“…The prevalence rate of anxiety and depression in the Indian population has increased in recent times, which is further amplified by the current circumstances. The prevalence rate of anxiety disorders in India, based on a meta-analysis with a sample size of 33 572 samples, is 5.8% with a higher prevalence in urban communities as compared to the rural ones (3). Anecdotal evidences of psychologists and therapists also show how these cases have been on the rise ever since the advent of the virus and due to increase in uncertainties around jobs, health concerns, and ability to perform daily tasks.…”
mentioning
confidence: 99%
“…This prejudice from family member may have led to increase children anxiety level in gender also. 17,30 The confirmatory factor analyses suggested that PAS 28 items reflect the dimensions of social phobia, separation anxiety, obsessivecompulsive disorder, fears of PIF, and generalized anxiety, provide a poor fit of the data. However, the five factors correlated model was found to be a good fit in different studies conducted in Austrian, Romanian and Chinese.…”
Section: Discussionmentioning
confidence: 99%